21st century astronomy - Kay, Laura (Norton & Company, 2006)
The fourth edition of 21st century astronomy helps students use the process of science to understand how the physical principles were used in the discovery of the origins of the universe. The authors emphasize how we know what we know in the figures, text, and end of chapter material. SmartWork challenges students to apply what they have learned and allows instructors to track their progress.; Quỹ Châu Á